A Scoping Review on Understanding Climate Change’s Effects on Pregnancy in Coastal Regions - Setyani, Enrika Rahayu; Rusprayunita , Nurendah Ratri Azhar; Wahab, Abdul (Universitas Airlangga, 2024)
Introduction: Pregnancy increases vulnerability to environmental stressors. Climate change heightens risks for pregnant women, leading to adverse maternal and infant outcomes. Coastal regions, prone to sea-level rise, rising temperatures, saltwater intrusion, and extreme weather, face significant health impacts. This review summarises the effects of climate change on pregnant women in these areas, emphasising the need for targeted interventions to mitigate these risks. Discussion: This scoping review was conducted using the advanced Arksey and O’Malley framework. Utilizing several keywords, including 'climate change,' 'adverse pregnancy,' 'pregnant outcome,' 'coastal,' and 'island,' a thorough exploration was conducted on PubMed, ScienceDirect, Scopus and ProQuest. A thorough review of 660 articles from 2020–2024 on those online databases identified 34 relevant studies. The findings show that coastal residents face environmental challenges such as rising temperatures, air pollution, cyclones, hurricanes, ozone exposure, floods, and highly saline water. Prolonged exposure to these conditions exacerbates health risks. Climate change is linked to adverse pregnancy outcomes, including low birth weight, small gestational age, stillbirth, preterm birth, neonatal health problems, and increased the risk of pregnancy complications and miscarriages. Conclusion: Climate change significantly affects pregnant women, causing complications and adverse outcomes throughout pregnancy. Addressing these issues requires comprehensive policies and intervention programs. These insights provide a foundation for policymakers to develop strategies that support and protect pregnant women in vulnerable regions. Household-level efforts, such as providing a comfortable living environment, can help reduce the climate change impacts.